Here in Harlem : poems in many voices - Myers, Walter Dean, 1937-2014. (New York : Holiday House, 2004)
Acclaimed writer Walter Dean Myers celebrates the people of Harlem with these powerful and soulful first-person poems in the voices of the residents who make up the legendary neighborhood: basketball players, teachers, mail carriers, jazz artists, maids, veterans, nannies, students, and more. Exhilarating and electric, these poems capture the energy and resilience of a neighborhood and a people.
Keywords: African Americans -- Poetry; Young adult poetry, American; American poetry; Harlem (New York, N.Y.) -- Poetry